Analysis of the Influence of Technology, Information, and Communication Developments on Economic Growth in Java Island 2018 – 2022 - Elang, Elang Mulya Maulana; Kusuma, Hendra (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
This study aims to analyze the influence of the number of cellular phone users, internet users, e-commerce users, and labor force on economic growth in Java. This research is included in quantitative research. The data used in this study is panel data, which comes from a combination of cross-section data from 6 provinces on Java Island and data. In this study, the data analysis technique used is panel data regression analysis to determine the effect of technology, information, and communication variables on economic growth variables. Panel data is a combination of time series data and cross-section data. The results showed that the number of cellular phone users had a positive and significant effect on economic growth, while the number of Internet users and E-Commerce users had a significant negative effect on economic growth, while the labor force had a positive and insignificant effect on economic growth.